The flying Dutchman - Scholtz, Calvin (Department of English Language and Literature, 2014)
A Dutch sea-captain and his crew wake up on the deck of their VOC ship in the middle of the ocean with no memory of who they are or how they got there. Howe ver, one of the sailors does remember their captain's name: Heinrich van der Decken. Then they discover a port nearby: it is Simon's Town, South Africa, and the year is 2012. The man sent by the SA Navy to meet the foreign visitors is Commander Paul Jones, who is surprised by the old sailing ship and its crew of sailors dressed as though they'd stepped out of a pirate film. Jones decides that they must be historians sailing their antique vessel on a recreation of the voyage of some famous explorer. He offers to help them in any way he can, starting with lunch at a local restaurant. It is at this restaurant that Captain van der Decken meets Elbé Abrahams, a waitress who looks exactly like Senta, a slave that he fell in love with in Holland. The captain tries to talk to her, but she rebuffs him, saying she has never met him before. When she leaves the restaurant, van der Decken follows her home. As the captain sees more of Elbé, the more he remembers about his past. The more Elbé sees of him, the more she finds herself drawn to him. And the more van der Decken learns, the more he realises that someone is responsible for imperilling the lives of himself and his crew, and that a battle that has been anticipated for centuries will finally be fought. The author seeks to explore and combine two legends of the Cape of Good Hope, that of The Flying Dutchman and Adamastor, through the medium of fiction. The author attempts an imaginative retelling of these legends by having them play out in the year 2012, recasting an old story for a new age, while remaining close to their geographical point of origin, the Cape of Storms. The novel is rounded out by two modern characters, from whose perspectives the story is sometimes seen: Paul Jones, a thirty-something commander in the South African Navy, and Elbé Abrahams, a nineteen-year-old girl who is still trying to decide on her path in life, and whose destiny may be bound up with that of the Dutch sea-captain, van der Decken.